Fungi Fibrinolytic Compound 1 Plays a Core Role in Modulating Fibrinolysis, Altering Plasma Clot Structure, and Promoting Susceptibility to Lysis - Chunli Gao; Bin Bao; Chunling Bao; Wenhui Wu (MDPI AG, 2023)
Fibrin clot structure and function are major determinants of venous and arterial thromboembolic diseases, as well as the key determinants of the efficiency of clot lysis. Studies have revealed that fungi fibrinolytic compound 1 (FGFC1) is a novel marine pyranisoindolone natural product with fibrinolytic activity. Here, we explore the impacts of FGFC1 on clot structure, lysis, and plasminogen activation in vitro using turbidimetric, enzyme-linked immunosorbent assay, confocal and electron microscopy, urokinase, or plasmin chromogenic substrate. Clots formed in the presence of FGFC1 expressed reduced fibrin polymerization rate and maximum turbidity; however, they did not influence the lag phase of fibrin polymerization. In the absence of scu-PA (single-chain urokinase plasminogen activator), microscopy revealed that FGFC1 increased the number of protofibrils within fibrin fiber and the pore diameter between protofibrils, inducing clots to form a region of thinner and looser networks separated by large pores. The effects of FGFC1 on scu-PA-mediated plasma clot structure were similar to those in the absence of scu-PA. In addition, FGFC1 promoted the lysis of clots and increased the D-dimer concentration in lysate. FGFC1 increased the generation rate of p-nitroaniline in plasma. These results show that FGFC1 has fibrinolytic activity in plasma, leading to interference with the release of fibrinopeptide B to affect lateral aggregation of protofibrils and increase clot susceptibility to fibrinolysis by altering its structure.